The role of academic procrastination as factor of university abandonment - Garzón Umerenkova, Angélica; Gil Flores, Javier (Revista Complutense de Educación, 2016)
Trends in the research of academic procrastination and what these perspectives can offer to understand university abandonment are presented in this paper through a theoretical revision. Procrastination is the delaying of performing something that should be done and as such, it is a selfregulation failure in time management behavior. Initially, a definition of university abandonment or college desertion is provided together with the variables and theoretical models used for its explanation; also, the main figures related to student enrollment and desertions are presented. Secondly, the self-regulating academic models which have been used to study the procrastination are also presented, and finally, the main findings and perspectives in procrastination interventions are defined. To promote the increase of academic retention, it is convenient, besides the study of traditional variables associated to college desertion, to incorporate new variables that provide conceptual tools to the explanation and prevention of this phenomenon. This is the case in academic procrastination. It is demonstrated in this paper that there is evidence of the association between high levels of procrastination and low academic performance in students, that it is a competency that can be assessed as an entry requirement for college, that it could be successfully trained and that its improvement, in the context of self-regulated learning, entails not only academic benefits but it also enhances students quality of life.